New data on the study of the Tasmola archaeological culture of Saryarka - Habdulina Марал (Turkic Studies Journal, 2021)
The article presents historical and cultural reconstructions of the research results of the last decades of the Tasmola archaeological culture of Central Kazakhstan. Tasmola archaeological culture in the frame work of the VII-III centuries BC was highlighted by M.K. Kadyrbaev in 1966. Currently, the Tasmola culture source data base has been replenished with new types of archaeological sites: “royal” mounds, settlements, stone statues. An analysis of them using new natural-science methods makes it possible to make adjustments to the culturalal and chronological periodization of the Saka era of the Saryаrka, and to consider the canons of the barrower chitecture of then nobility and the compositional structure of the living space of the steppe nomads. The archaeological classification of artifacts, radiocarbon analyzes date the Tasmola culture on the 8th-6th centuries BC. At this time, large elite barrows appear, the architectural style of settled monument sis emerging, which has been preserved until modern times, until the Kazakhs’ wintering (kystau). Study of the structure of the land part of elite memorials confirms the concept of the early Saka barrow tradition as architecturally complex and multi functional religious buildings. The stone sculptures of the Tasmolatribes’ are characterized by a complex of signs that distinguish the min to a separate group of ancient statuary art of the Scythian-Saka era.